1999
DOI: 10.26686/nzaroe.v0i9.1378
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Resource Teachers in New Zealand: A Quarter Century of Paradigm Change

Abstract: The purpose of this paper is to trace the development of the role of Resource Teachers Learning and Behaviour (RTLB) from its genesis in the establishment of the Guidance and Learning Units in 1975, through the establishment of support teams and Resource Teacher Special Needs to its present form. This development is placed in the context of two paradigm shifts that have impacted on special education practice and policy in New Zealand over the last 25 years. The somewhat halting progress of special education is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…This is contrary to commonly held beliefs in the US in which ADHD is considered to be a distinct biologically based condition that frequently co-occurs with learning disabilities (Nigg & Casey, 2005). The literature suggests that teachers in NZ may focus their intervention(s) on changes in teaching methods or upon improving literacy skills in the classroom, relegating behaviour management to a secondary function (Brown et al, 2012;McGee & Share, 1988;Stanton et al, 1990;Thomson, Brown, Jones, & Manins, 2000). Brown and colleagues' (2012) study, which enlisted a nationally representative sample of NZ teachers, reported teacher beliefs and learning orientations that were consistently in line with the objectives of NZ educational policies.…”
Section: Societal and Cultural Contexts For Teacher Beliefsmentioning
confidence: 50%
See 2 more Smart Citations
“…This is contrary to commonly held beliefs in the US in which ADHD is considered to be a distinct biologically based condition that frequently co-occurs with learning disabilities (Nigg & Casey, 2005). The literature suggests that teachers in NZ may focus their intervention(s) on changes in teaching methods or upon improving literacy skills in the classroom, relegating behaviour management to a secondary function (Brown et al, 2012;McGee & Share, 1988;Stanton et al, 1990;Thomson, Brown, Jones, & Manins, 2000). Brown and colleagues' (2012) study, which enlisted a nationally representative sample of NZ teachers, reported teacher beliefs and learning orientations that were consistently in line with the objectives of NZ educational policies.…”
Section: Societal and Cultural Contexts For Teacher Beliefsmentioning
confidence: 50%
“…By comparison, the NZ Ministry of Education declared a national mission in the 1970s to move away from segregated special education services and to promote an ecological orientation to educational policies and practices (Thomson et al, 2000). Consequently, a program called Special Education 2000 was later developed with the aim to achieve a world-class inclusive education system that provides learning opportunities of equal quality for all students (New Zealand Ministry of Education, 1996, p. 5).…”
Section: United States and New Zealand Educational Modelsmentioning
confidence: 98%
See 1 more Smart Citation
“…Although special education in New Zealand had been evolving over the last 25 years (Thomson, Brown, Jones, & Manins, 2000), the approach at the time the policy was announced was conceptualised by the programme developers as mainstreaming, which differs significantly from inclusion. Mainstreaming is a process whereby students with special needs, who have previously been excluded, are placed in regular classrooms, whereas inclusion is a process of school reform that requires organisational and instructional change to meet the needs of a diverse range of students.…”
Section: Context Of Studymentioning
confidence: 99%
“…8. ' Macfarlane, Brown & Thomson, 1999;Thomson, Brown, Jones & Manins, 2000) that focused on collaborative problem solving in mainstream classrooms. The RTLB training programme responded to the concerns of Māori that the education system was not sufficiently responsive to Māori cultural values and practices (Macfarlane, 2000(Macfarlane, , 2004Macfarlane, Glynn, Cavanagh & Bateman, 2007).…”
Section: The New Zealand Contextmentioning
confidence: 99%